Effects of sebum properties on skin friction: investigation using a bench test. Issue 2 (16th June 2020) - Korbeld, Kerlen T.; Klaassen, Michel; Jobanputra, Rikeen D.; de Vries, Erik G.; Masen, Marc A.
Abstract : The hydro lipid film is an emulsion of sweat and sebum that covers the surface of the human skin and affects the tribological properties of the human skin. This study investigates the effects of the composition of the sebum on the average coefficient of friction. A range of simplified sebums was developed and the friction behaviour was investigated. Five realistic sebums showed a strong variation in friction results, indicating that interpersonal differences in frictional behaviour might have their origin in differences in sebum composition. A more detailed investigation employing controlled variations of individual ingredients showed that friction is highly sensitive to the amount of squalene in the sebum. The amount of fatty acids in the sebum also showed some effects, whilst the amount of cholesterol does not appear to be relevant for the friction behaviour. The main new outcome from this study is that the composition of sebum has a significant effect on the friction response of skin in ways that are currently not yet fully understood.